DEKOLORISASI LIMBAH BATIK MENGGUNAKAN LIMBAH MEDIUM TANAM Pleurotus ostreatus PADA WAKTU INKUBASI YANG BERBEDA - Fitriya Yuni Wulandari; Nuniek Ina Ratnaningtyas; Ratna Stia Dewi (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
The batik waste industry is one source of water pollution. It must undergo treatment before discharge into the environment. Batik waste treatment technologies can be done biologically, chemically, physically, or combination of three processes. This research applied a combination of biology and physic technologies, namely used spent mushroom of Pleurotus ostreatus as the decolorization agent. Mycelium of P. ostreatus was used as biological agent, and cellulose from spent mushroom was used as physical agent. The aims of this research were to determine the effect of spent mushroom with variation incubation time on batik waste decolorization, and to know the optimum incubation time with highest decolorization batik waste percentage using spent mushroom of P. ostreatus. This research used experimental method with completely randomized design (CRD). The data obtained were statistically analyzed using Varian Test (ANOVA) on confidence level of 95% and 99% and continued with Honest Significant Difference Test (BNJ) with 95% confidence level. The result showed that variation incubation time treatment of batik waste decolorization used spent mushroom of P. ostreatus provide a highly signification effect on batik waste decolorization. The optimum incubation time was 60 hour (LW5), with decolorization percentage was 85,64%.